Selective Hydrogenation of the Carbonyls in Furfural and 5-Hydroxymethylfurfural Catalyzed by PtNi Alloy Supported on SBA-15 in Aqueous Solution Under Mild Conditions - Gao, Ge; Jiang, Zhicheng; Hu, Changwei (Frontiers in Chemistry, 2021)
Valuable furfuryl alcohol (FFA) and 2,5-dihydroxymethylfuran (DHMF) could be produced by selective hydrogenation of biomass-derived furfural (FF) and 5-hydroxymethylfurfural (HMF) with high atom economy. In this study, SBA-15 (a kind of mesoporous silica molecular sieve)-supported low metal loading (3 wt% total metal content) PtNi alloy catalyst (PtNi/SBA-15) was synthesized via two steps, including the generation of PtNi alloy by hydrothermal method, and the immobilization of PtNi alloy on SBA-15. PtNi/SBA-15 has ordered mesoporous structure with high surface area, and high dispersion of the PtNi alloy with the formation of Ptδ--Niδ+ surface pairs on SBA-15, which benefit hydrogen activation and selective carbonyl hydrogenation. The selective hydrogenation of FF and HMF over PtNi/SBA-15 in water solvent at 303 K with 1.5 MPa H2 within 2 h, could respectively yield 64.6% FFA with 77.0% selectivity, and 68.2% DHMF with 81.9% selectivity. Besides, PtNi/SBA-15 exhibited a satisfactory water resistance and stability after recycling at least five runs.